Managing the Design Innovation-Brand Marketing Interface: Resolving the Tension between Artistic Creation and Commercial Imperatives - Beverland, Michael B. (The Journal of product innovation management)
The relationship between design and marketing is an uneasy one. Managing this tension is critical for luxury marketers, whose point of differentiation is a combination of design excellence and market execution. This article explores the tensions between marketing and design and the integration of design into the brand management process in luxury wine firms. The results of the investigation describe five design‐based values held by luxury winemakers: remaining true to craft, expressions of place, stylistic consistency, living up to the brand's heritage, and remaining current. Five methods of integrating design into the firm are identified. These are top leadership support and integration at the strategic level, simultaneous loose–tight coupling, being in the marketplace versus being of the marketplace, intergenerational teams, and deliberate decoupling. This last is a novel solution and involves designers walking a fine line between their commitment to their values and the ongoing evolution of the brand. Essentially, designers of luxury wine products downplay their scientific expertise, market knowledge, and responsiveness in favour of appealing to their five espoused values.